2015
DOI: 10.1186/s13014-015-0460-2
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenectomy in women with endometrial cancer: aspiration and reality from a radiation oncologist’s point of view

Abstract: BackgroundTo investigate the meaning of lymphadenectomy (LNE) in women with endometrial cancer (EC) for clinical outcome and secondly to determine the impact of the method of adjuvant radiotherapy (RT) on survival as well as to define prognostic factors.Methods322 patients (pts) underwent adjuvant RT for endometrioid EC at our department from 2004 until 2012 and were included in this retrospective study. Chi-square test, LogRank test and Cox regression were used for statistical analyses.ResultsMedian age at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…On other hand, our study found a significant association between radiotherapy management and women underwent NSSS (p=0.05). This finding is similar to the results of Foerste et al 36 which reported that standard was rarely used in women with endometrial carcinoma subjected to adjuvant radiotherapy and this led to poor prognosis 36 . A small sample size has reduced the statistical power of the survey study, this could be justified by the limited duration of the time, the pandemic of COVID-19, and poor data documentation in the cancer center having greater impact on the data collection.…”
Section: Discussionsupporting
confidence: 91%
“…On other hand, our study found a significant association between radiotherapy management and women underwent NSSS (p=0.05). This finding is similar to the results of Foerste et al 36 which reported that standard was rarely used in women with endometrial carcinoma subjected to adjuvant radiotherapy and this led to poor prognosis 36 . A small sample size has reduced the statistical power of the survey study, this could be justified by the limited duration of the time, the pandemic of COVID-19, and poor data documentation in the cancer center having greater impact on the data collection.…”
Section: Discussionsupporting
confidence: 91%